How many fast-charging stations do we need along European highways?. (August 2019) - Jochem, Patrick; Szimba, Eckhard; Reuter-Oppermann, Melanie
Highlights: Minimum number of fast-charging stations along the highway network are identified. An flow-refueling location model (FRLM) is applied. The model uses a comprehensive flow dataset of the European highway network. The operation of fast-charging stations is going to be highly profitable. The workload is widely unequally distributed between these charging stations. Abstract: For a successful market take-up of plug-in electric vehicles, fast-charging stations along the highway network play a significant role. This paper provides results from a first study on estimating the minimum number of fast-charging stations along the European highway network of selected countries (i.e., France, Germany, the Benelux countries, Switzerland, Austria, Denmark, the Czech Republic, and Poland) and gives an estimate on their future profitability. The combination of a comprehensive dataset of passenger car trips in Europe and an efficient arc-cover-path-cover flow-refueling location model allows generating results for such a comprehensive transnational highway network for the first time. Besides the minimum number of required fast-charging stations which results from the applied flow-refueling location model (FRLM), an estimation of their profitability as well as some country-specific results are also identified. According to these results the operation of fast-charging stations along the highway will be attractive in 2030 because the number of customers per day and their willingness to pay for a charge is high compared to inner-city charging stations. Their location-specific workloads as well as revenues differ significantly and a careful selection of locations is decisive for their economic operation.